1978
DOI: 10.1007/bf01851939
|View full text |Cite
|
Sign up to set email alerts
|

Complement system in sodium taurocholate pancreatitis in the rat

Abstract: The role of the complement system was studied in Na-taurocholate pancreatitis in rats. Complement activity (CH 50) was determined at various times in the course of pancreatitis. Immediately after induction of acute pancreatitis, serum complement activity declined and massive C 3 deposits could be detected in the vicinity of acinar necroses and necrobioses. After a phase of recovery three to six hours postoperatively a second complement consumption occurred. Lethality rate increased as serum complement activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Only severe necrotizing pancreatitis, but not mild edematous AP, in rats was accompanied by early complement activation with increased levels of C3a (48). Similar results linking decreasing complement hemolytic activity (CH50), acinar C3 deposits, and histological tissue damage could be found in a rodent model of AP (49). It is noteworthy that complement consumption in early AP can be accompanied by persistently lowered serum complement levels several weeks after the onset of symptoms (50).…”
Section: Complement In the Pathophysiology Of Apsupporting
confidence: 78%
“…Only severe necrotizing pancreatitis, but not mild edematous AP, in rats was accompanied by early complement activation with increased levels of C3a (48). Similar results linking decreasing complement hemolytic activity (CH50), acinar C3 deposits, and histological tissue damage could be found in a rodent model of AP (49). It is noteworthy that complement consumption in early AP can be accompanied by persistently lowered serum complement levels several weeks after the onset of symptoms (50).…”
Section: Complement In the Pathophysiology Of Apsupporting
confidence: 78%
“…In sodium taurocholate pancreatitis, edema and necroses develop early in the disease, followed by leukocyte infiltration [32]. According to Wanke [33], bile salt-induced pancreatitis develops in two stages.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data suggest that the complement system exerts important roles in several diverse processes. In addition to its classical role in microbial defense, complement can recruit neutrophils and regulate inflammation and tissue damage in different inflammatory conditions [11][12][13][14][15]. C3 is the central molecule of complement, positioned at the crossroad of all the complement activation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that trypsin can cleave C3 and facilitate leukocyte activation [16]. Deposition of C3 on acinar cells and histological damage of acinar cells were shown to increase in the taurocholate-induced model of AP [11]. In addition, in an endotoxin model of brain injury, C3-deficient mice exhibited decreased neutrophil recruitment and endothelial activation [15].…”
Section: Introductionmentioning
confidence: 99%